Association of the Type, Amount and Frequency of Milk Feeding with Anthropometric Growth Indicators in Infants - Khan, Rida; Farooq, Fatima; Tanweer, Afifa; Chughtai, Amina (Progress in Nutrition, 2022)
Infant feeding practices during early days of life are considered crucial as they may have an impact on growth and development later in life. A cross-sectional study was conducted on 150 infants aged 0-4 months, in Lahore, Pakistan to find out the association between milk feeding practices and anthropometric growth indices. Data was collected through interviewer administered questionnaire for 24-hour dietary recall and WHO growth charts for anthropometric assessment. The average breastfeeding time for normal weight for length infants was significantly (p=0.014) higher (9.850±3.907) than wasted infants. Infants with normal length for age were breastfeed for significantly (p=0.009) longer time (9.768±3.993) as compared to stunted infants (8.000±3.045). Normal weight for age infants had significantly (p=0.015) shorter breastfeeding interval (83.767±37.228) as compared to underweight infants (103.750±25.527). Infant milk feeding practices was found to be linked to the nutritional status. Breastfed infants had better growth outcomes as compared to non-breastfed. Promotion of breastfeeding practices may warrant good nutritional status in infants and thus can be regarded as one of the strategies for tackling the short term and long-term burden of malnutrition.